Physical Exercise In Schizophrenia - Tanjung Ayu Sumekar; Hang Gunawan Asikin (Diponegoro International Medical Journal, 2025)
Background: Schizophrenia is a mental disorder characterized by positive and negative symptoms, with antipsychotics effectively addressing the former but less so the latter. Recent studies suggest that physical exercise may help alleviate negative and cognitive symptoms, though its role is not well established.Objective: This review examines the role of physical exercise as a complementary intervention in the psychosocial rehabilitation of individuals with schizophrenia.Methods: A narrative literature review was conducted, focusing on research exploring the effects of various exercise types on psychiatric symptoms, cognitive function, and physical health in individuals with schizophrenia.Results: Physical exercise was found to improve cognitive function, reduce negative symptoms, and mitigate the metabolic side effects of antipsychotic medications. Neurobiological changes, such as increased neurogenesis and synaptic plasticity, were also observed, contributing to better mental health and quality of life. Aerobic and anaerobic exercises were particularly effective in reducing psychiatric symptoms and enhancing social integration.Conclusion: Physical exercise offers significant benefits in schizophrenia care and should be integrated into multidisciplinary treatment strategies. Future research should focus on optimizing exercise protocols and assessing their long-term clinical impact.